2021
DOI: 10.1108/jopp-04-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

Broader outcomes in procurement policy – a case of New Zealand pragmatism

Abstract: Purpose The purpose of this paper is to investigate how the underpinning ideas of public procurement allowed for broader outcomes – a more strategic form of public procurement – to emerge. The paper contributes to the literature on public procurement by empirically addressing the evolution of procurement as a government policy lever in New Zealand so as to demonstrate how policy pragmatism can ensure a shift without a complete overhaul of a complex system. Design/methodology/approach The paper has used a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Instead, the US federal government has been able to invest billions of dollars in small firms and encountered no substantive performance differences (and may even see performance benefits in some industries). Other studies have shown that public procurement programs are improving social and economic outcomes in communities of color and for women (Allen, 2021; McIver et al, 2018; Ryu & Sueyoshi, 2021). Yet worries persist that procurement equity programs incur hidden performance risks for governments.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the US federal government has been able to invest billions of dollars in small firms and encountered no substantive performance differences (and may even see performance benefits in some industries). Other studies have shown that public procurement programs are improving social and economic outcomes in communities of color and for women (Allen, 2021; McIver et al, 2018; Ryu & Sueyoshi, 2021). Yet worries persist that procurement equity programs incur hidden performance risks for governments.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarly and policy focus on public procurement is the result of several interlinked factors. First, there is appreciation of the strategic role that procurement plays in public administration and public service delivery: strategic in the sense that procurement can help public sector organisations achieve their corporate objectives related to cost containment, service delivery and socio-economic objectives (Allen, 2021; Glas et al , 2017). Second, procurement spend is recognised as important in giving effect to what Arrowsmith (2010) called “horizontal policies”.…”
Section: Evolution Of Public Procurementmentioning
confidence: 99%
“…Academic understanding of public procurement has evolved over the last twenty years. From its earlier status as an administrative function, there is now recognition of the strategic role that public procurement can play in achieving value for money (VfM), delivering improved services for end-users and supporting government sustainability objectives (Allen, 2021; Glas et al , 2017). It remains to be seen whether the media has represented public procurement in these same ways or if it has taken a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…Public sector procurement is identified globally as a key source of value creation for governments and their agencies through the function's cost-saving potential. The strategic importance of procurement to public administration through its support to public sector institutions toward achieving their mandates relative to cost containment, service delivery and other socio-economic objectives has been widely recognized in the literature (Allen, 2021;Flynn and Harris, 2022;Glas et al, 2017). Despite its rich history as well as its strategic importance, the recognition of procurement within the academic circles is a very recent development.…”
Section: Introductionmentioning
confidence: 99%